Delivery of MiR335‐5p‐Pendant Tetrahedron DNA Nanostructures Using an Injectable Heparin Lithium Hydrogel for Challenging Bone Defects in Steroid‐Associated Osteonecrosis. Issue 1 (1st November 2021) - Li, Donghai; Yang, Zhouyuan; Luo, Yue; Zhao, Xin; Tian, Meng; Kang, Pengde
Abstract: Corticosteroids‐induced Dickkopf‐1 (DKK1) upregulation and Wnt signaling inhibition result in bone metabolism disorder and steroid‐associated osteonecrosis (SAON). Implanting biomaterials to regulate the Wnt pathway is a promising method to repair challenging bone defects associated with SAON. Here, tetrahedral DNA nanostructures (TDNs) are fabricated as gene carriers to deliver MiR335‐5p, which targets DKK1 translation. Heparin lithium hydrogel (Li‐hep‐gel) is synthesized to act as a lithium and MiR@TDNs delivery agent. Finally, the repair effects on challenging bone defect in SAON using a MiR@TDNs/Li‐hep‐gel composite are assessed in vivo. The results reveal that MiR@TDNs are absorbed by bone mesenchymal stem cells (BMSCs) and increase cell viability and reduce apoptosis. Moreover, MiR@TDNs promote alkaline phosphatase expression and calcium nodular deposition, decrease lipid droplet expression of BMSCs, and improve vascular endothelial growth factor secretion and vascular‐like structure formation in vitro. After MiR@TDNs/Li‐hep‐gel is implanted into the SAON model, the internal bone defect of osteonecrosis is repaired with a large area of new bone accompanied with neovascularization and reduced empty lacunae. In conclusion, MiR@TDNs/Li‐hep‐gel can provide dual delivery of lithium and MiR@TDNs, which synergistically upregulate the Wnt signaling pathway, enhancing bone regeneration in challenging bone defects, and can be potentially used in SAON repair. Abstract : The MiR@TDNs/Li‐hep‐gel synergistically upregulates the Wnt signaling pathway by dual delivery of lithium and MiR335‐5p@TDNs, which improves the osteogenesis and angiogenesis, contributing to enhanced bone regeneration and repairing of challenging bone defects in steroid‐associated osteonecrosis (SAON).